"You gotta give them hope": A structural psychobiography of Harvey Milk (1930–1978). Issue 1 (5th December 2022) - Weststrate, Nic M.; McLean, Kate C.
Abstract: Objective: In this psychobiographical study, we examined the life and times of social change agent Harvey Milk, one of the first openly gay public officials in the United States. Milk is remembered as a gay hero who fought for the rights of marginalized people, often by invoking the importance of hope. Milk was assassinated less than 1 year after his election. Method: We adopt a structural psychobiographical approach, foregrounding social, cultural, political, and historical forces that intersect with personal factors to explain Milk's ascension to the status of social change agent. Results: This psychobiography tells the story of a man not destined to become a social change agent but who became one anyway because of shifting tides in the political climate of San Francisco in the 1970s, because of a series of catalytic events that started him down this path, because of a history of persecution as a gay Jew, and because of his enduring need for a stage upon which he could express his generative concern. Conclusions: Our analysis raises questions about the story that "belongs" to the agent of social change, and the story that "belongs" to the rest of us, as we remember him.